1997
DOI: 10.1093/ptj/77.3.260
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Incentive Spirometry With Physical Therapy for High-Risk Patients After Coronary Artery Bypass Surgery

Abstract: Incentive spirometry combined with physical therapy is no more effective than postoperative physical therapy alone in reducing atelectasis for this population. Use of the spirometer, however, was not monitored, and although the study mimicked practice as it often occurs, the effectiveness of the spirometer cannot be fully evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 20 publications
2
71
0
9
Order By: Relevance
“…Findings on pleural effusion are also frequent. It was found at a rate of 32% and 43.9% on the 2 nd and 3 rd postoperative day (POD), respectively [20]. Westerdahl et al [21] found it in 63% of patients on the 4 th POD, data similar to the study of Vargas et al [38], on which the authors used TCT as preliminary tool.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Findings on pleural effusion are also frequent. It was found at a rate of 32% and 43.9% on the 2 nd and 3 rd postoperative day (POD), respectively [20]. Westerdahl et al [21] found it in 63% of patients on the 4 th POD, data similar to the study of Vargas et al [38], on which the authors used TCT as preliminary tool.…”
Section: Resultsmentioning
confidence: 63%
“…Lung infections, whose prevalence ranges between 3.5% [23] and 10% [20], also contribute to the morbidity related to HS. Westerdahl et al [22] found no signs of lung infection in any of the patients the authors included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations